2022
DOI: 10.1007/s40123-022-00574-z
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic vs. Single Image Analysis with Confocal Microscopy of the Corneal Nerve Plexus for Diagnosis of Early Diabetic Peripheral Neuropathy

Abstract: Introduction:The assessment of the corneal nerve fibre plexus with corneal confocal microscopy (CCM) is an upcoming but still experimental method in the diagnosis of early stage diabetic peripheral neuropathy (DPN). Using an innovative imaging technique-Heidelberg Retina Tomograph equipped with the Rostock Cornea Module (HRT-RCM) and EyeGuidance module (EG)-we were able to look at greater areas of subbasal nerve plexus (SNP) in order to increase the diagnostic accuracy. The aim of our study was to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
3
1
Order By: Relevance
“…Our automated imaging and quantification methods and strict inclusion of participants of the same age and only with type 2 diabetes may account for these differences; however, more studies without requiring selection of single IVCM images are warranted to verify our findings. Two earlier studies with substantially smaller imaged areas than in the current study also reported poor correlation of IVCM with IENFD or neuropathy disability ( 34 , 35 ). Use of corneal nerves as a surrogate marker for detecting neuropathy in diabetes should therefore be considered with caution, and studies should be assessed based on the area of the subbasal nerve plexus imaged and the potential for bias in selection of nerve images for analysis.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Our automated imaging and quantification methods and strict inclusion of participants of the same age and only with type 2 diabetes may account for these differences; however, more studies without requiring selection of single IVCM images are warranted to verify our findings. Two earlier studies with substantially smaller imaged areas than in the current study also reported poor correlation of IVCM with IENFD or neuropathy disability ( 34 , 35 ). Use of corneal nerves as a surrogate marker for detecting neuropathy in diabetes should therefore be considered with caution, and studies should be assessed based on the area of the subbasal nerve plexus imaged and the potential for bias in selection of nerve images for analysis.…”
Section: Discussioncontrasting
confidence: 73%
“…All subsequent quantitative analyses are ultimately limited by the subjective choice of images. These methodological deficiencies can have a large impact on the results obtained ( 31 , 35 ), and this may be limiting corneal nerve assessment in achieving the level of maturity and widespread acceptance as clinical measures of DPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampling strategy of adequate images has been shown to produce sufficient accuracy, however for longitudinal or clinical monitoring purposes, real-time widefield imaging capabilities may provide more insight into regional changes in the cornea over time or following exposure to various stimuli 77,78 . In fact, a minimum repeatable area of 1.5 mm 2 is shown to have reliable morphological characterisation of the sub-basal nerve plexus 79,80 .…”
mentioning
confidence: 97%